Relative age effect in junior tennis (male) - Agricola, A.; Zhánel, J.; Hubácek, O. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
The issues of the age effect (the theory of the age influence) have been shown in sport sciences since the 1980s. The theory of age effect works on the assumption that athletes born in the beginning of a calendar year are, particularly in children`s and junior age, more successful than athletes born in the end of the year. This fact has been proved by a number of research studies, mainly in ice hockey, soccer, and tennis but also in other sports. OBJECTIVE: The submitted contribution is aimed at verifying of the age effect in junior tennis. The research objective was to find out the distribution of birth date frequencies in a population of tennis players` in individual months, quarters, and half-years in the observed period 2007-2011 and to check the significance of differences. METHODS: The research was conducted on male tennis players aged 13-14 (N = 239), participants of the World Junior Tennis Finals. From the methodological point of view, it was an intentional selection. The birth dates of individual tennis players were taken from official materials of the ITF, the research data were processed using Microsoft Excel. The personal data were processed with the approval of players and the hosting organization (ITF). RESULTS: Testing of the hypothesis on the significance of differences in the distribution of frequencies between individual quarters (Q1-Q4) has proved statistically relevant differences between Q1 and Q3, Q1 and Q4, Q2 and Q3, and Q2 and Q4; a statistically relevant difference has been also found in the distribution of frequencies between the first and second half of the year. On the basis of the results of the presented research, the age effect in the studied population of junior male tennis players can be regarded as significant. CONCLUSIONS: The results of the analysis of the research data confirm the conclusions of similar studies in other sports and prove that in the population of elite junior players, participants of WJTF 2007-2011, there is a pronounced dominance of players born in the first and second quarters, i.e. in the first half-year. The mentioned conclusions show the necessity of reflecting the age effect in sports practice as it can influence sports performance, especially at the junior level.